Morphological and Pomological Variability Analysis of Walnut (Juglans regia L.) Genetic Resources from the Middle and High Atlas of Morocco (Atlas Journal of Biology, 2018)
The walnut (Juglans regia L.) is a traditional fruit crop in Morocco. This species is cultivated in mountain in different environments. However, little data is available on its genetic diversity and its adaptability. Morphological characters of leaf and fruit from 11 Moroccan accessions of walnut were used to assess phenotypic variation of this species. Significant differences were found between accessions for the most examined traits, indicating a high phenotypic diversity. Multivariate analyses lead to identify three groups of accessions. The first group composed by the accessions of both Middle and High Atlas Mountain with high weigh and percentage of kernel and low thickness of shell. The second group included the accessions for the High Atlas Mountain characterised by large leaf, high nut dimension and great nut size. The third group is composed by two accessions, one belongs to the Middle Atlas Mountain and the other originating from High Atlas Mountain, which are characterized by small leaf and nut. Then, the structuration of accessions in three groups was not correlated to the mountain range type. Moreover, this study showed a significant phenotypic heterogeneity between the eleven studied accessions which opens the way for the strategies for their conservation and the selection of efficient genotypes with the desired traits.